1998
DOI: 10.1001/archsurg.133.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Lymphedema of the Extremities

Abstract: To define the immediate and long-term volumetric reduction following complete decongestive physiotherapy (CDP) for lymphedema. Design: Prospective study of consecutively treated patients. Setting: Freestanding outpatient referral centers. Patients: Two hundred ninety-nine patients referred for evaluation of lymphedema of the upper (2% primary, 98% secondary) or lower (61.3% primary, 38.7% secondary) extremities were treated with CDP for an average duration of 15.7 days. Lymphedema reduction was measured follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
1
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(180 citation statements)
references
References 10 publications
3
168
1
8
Order By: Relevance
“…In one of the larger studies of CDT (n 5 299 patients), researchers reported average reductions in limb volumes of 59% (for upper-extremity LE) and 68% (for lower-extremity LE). 7 …”
Section: Lymphedema Treatmentmentioning
confidence: 99%
“…In one of the larger studies of CDT (n 5 299 patients), researchers reported average reductions in limb volumes of 59% (for upper-extremity LE) and 68% (for lower-extremity LE). 7 …”
Section: Lymphedema Treatmentmentioning
confidence: 99%
“…Components of Combined, Complex or Comprehensive Decongestive Therapy include manual lymph drainage (MLD), multi-layer, short-stretch compression bandaging, lymphatic exercise, skin care, and education in lymphedema management as well as elastic compression garments (Didem et al, 2005;Ko, 1998). There are to phases of CDT: Phase I (Reductive) and Phase II (Maintenance).…”
Section: Non-invasive Management Techniquesmentioning
confidence: 99%
“…The first phase's frequency and duration should be altered as to produce the best possible outcome of improvements in skin and reduction in swelling of the affected area in the shortest time period. Normally, CDT is completed within 3 to 8 weeks and administered daily, or 5 days per week Ko, 1998;Yamamoto et al, 2008). The second phase of CDT is a self-management program is set up directly following completion of phase I.…”
Section: Non-invasive Management Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakao et al (2013) JIN et al, 2009;OASHI et al, 2012;HÄGERLING et al, 2013;KUWAHARA et al, 2013). Segundo Kazenwadel et al (2012) (SLAVIN et al, 1997;KO et al, 1998;SZUBA;ROCKSON, 1998). A linfangiogênese terapêutica tem sido vista como uma estratégia de tratamento com o potencial de reverter os estigmas da insuficiência linfática primária e secundária.…”
Section: Transcrição Reversaunclassified